The social relevance and social impact of knowledge and knowing. Issue 1 (February 2017) - Scaratti, Giuseppe; Galuppo, Laura; Gorli, Mara; Gozzoli, Caterina; Ripamonti, Silvio
In recent years, there has been a growing concern around the connection between theory and practice, rigour and relevance, theoretical consistency and impact. This Special Issue links with the literature on the co-production of knowledge and aims to extend the debate to the concept and practice of social value and social relevance, and their impact on different ways of knowing, researching and learning in organizations and in complex contexts and systems.